T regulatory cells and the control of alloimmunity: from characterisation to clinical application. - Wieckiewicz, J; Goto, R; Wood, K (2010)
T regulatory cells (Treg) play an important role in the induction and maintenance of immunological tolerance. Recent findings in experimental transplant models combined with the development of functional reporter mice have opened new avenues to study Treg biology and their therapeutic potential. In particular, recent advances in understanding Treg function and lineage stability revealed unexpected plasticity of this lineage. Nevertheless, pre-clinical and pilot clinical trials using Treg cells as cellular therapies have been initiated suggesting the safety and feasibility of such treatment.